A.3.
B.0.
C.2.
D. \(1\)
D
Ta có
\( \Leftrightarrow \left[ \begin{array}{\({4^{{x^2} - x}} + {2^{{x^2} - x + 1}} = 3 \Leftrightarrow {\left( {{2^{{x^2} - x}}} \right)^2} + {2.2^{{x^2} - x}} - 3 = 0 \Leftrightarrow {\left( {{2^{{x^2} - x}}} \right)^2} + {2.2^{{x^2} - x}} - 3 = 0\)l}{2^{{x^2} - x}} = 1\\{2^{{x^2} - x}} = - 3\left( {VN} \right)\end{array} \right. \Leftrightarrow {x^2} - x = 0 \Leftrightarrow x = 0;x = 1 \Rightarrow \left| {{x_1} - {x_2}} \right| = 1.\)
Đáp án D
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247